2011
DOI: 10.1063/1.3559223
|View full text |Cite
|
Sign up to set email alerts
|

Interface traps responsible for negative bias temperature instability in a nitrided submicron metal-oxide-semiconductor field effect transistor

Abstract: Articles you may be interested inBulk and interface trap generation under negative bias temperature instability stress of p-channel metaloxide-semiconductor field-effect transistors with nitrogen and silicon incorporated HfO 2 gate dielectrics Appl. Phys. Lett. 98, 063504 (2011); 10.1063/1.3541879 Identification of the atomic-scale defects involved in the negative bias temperature instability in plasmanitrided p -channel metal-oxide-silicon field-effect transistors Interface trap and oxide charge generation un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…Similar experimental results are also shown in Yonamoto et al work, in which they conclude that NBTI is due to an increase of the P b1 -center rather than the P b0 -center [17]. To summarize, the NBTI characteristics and mechanism in the SiO 2 /SiON are reviewed.…”
Section: Reliability Issue Of the Sion Gate Stacksupporting
confidence: 76%
See 1 more Smart Citation
“…Similar experimental results are also shown in Yonamoto et al work, in which they conclude that NBTI is due to an increase of the P b1 -center rather than the P b0 -center [17]. To summarize, the NBTI characteristics and mechanism in the SiO 2 /SiON are reviewed.…”
Section: Reliability Issue Of the Sion Gate Stacksupporting
confidence: 76%
“…the SiON is used to replace the SiO 2 in order to suppress the gate leakage and boron penetration. Many experimental results have shown that the presence of nitrogen in the gate oxide has substantially worsens the BTI performance [8,9,[16][17][18][19][20][21][22]. Kimizuka et al are those pioneers that conducting the NBTI study on the SiON device [9,23].…”
Section: Bias Temperature Reliability Of the Advanced Gate Stackmentioning
confidence: 99%
“…[9,10] More attention has been paid to this problem in recent years. [11][12][13] However, in spite of the intensive studies on the recovery issue, the physical mechanism is still far from being fully understood. In this paper, we study the recovery of NBTI systemically under different conditions in the 90-nm PMOSFETs, explain the various recovery phenomena, and find the possible processes of the recovery.…”
Section: Introductionmentioning
confidence: 99%